A more powerful non‐attribute‐specified sensory discrimination method: The paired unspecified tetrad with different order (AB and BA) pairs. Issue 5 (4th August 2020) - Bi, Jian; Kuesten, Carla
Abstract: The unspecified tetrad is a powerful non‐attribute‐specified sensory discrimination method widely used for sensory analysis and consumer research. A paired version of the method is proposed and explored in this article. It is the paired unspecified tetrad with different order (AB and BA) pairs. An analytical and a simulation‐derived psychometric function of the new method are produced. The paired unspecified tetrad with AB and BA pairs is more powerful than the conventional unspecified tetrad and the paired versions of the triangle and duo‐trio methods. A weakness of the paired version of the unspecified tetrad versus the conventional unspecified tetrad is that the new method involves in more adaption, fatigue, or memory factors. Practical Applications: The paired unspecified tetrad with different order (AB and BA) pairs has wide potential applications, especially for visual or manual inspection of food or nonfood products to detect before–after treatment effects, but may not be suitable for food tasting considering the adaption, fatigue, or memory factors.